2022
DOI: 10.1021/jacs.2c04527
|View full text |Cite|
|
Sign up to set email alerts
|

Palladium-Catalyzed Unimolecular Fragment Coupling of N-Allylamides via Elimination of Isocyanate

Abstract: Transition metal-catalyzed unimolecular fragment coupling (UFC) is defined as processes that forge new chemical bonds through the extrusion of molecules, such as CO and CO2, and the subsequent recombination of the remaining fragments. Herein, we report on a new UFC reaction that involves the palladium-catalyzed elimination of an isocyanate fragment from an amide, with the formation of carbon–carbon and carbon–heteroatom bonds. An organometallic intermediate that is relevant to the catalytic reaction was charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 100 publications
0
14
0
Order By: Relevance
“…A potential solution is the coupling of a carboxylic acid ester with an amine-derived (via N -alkyl pyridinium salts) or alcohol-derived (via alkyl halide) alkyl radical source under nickel-catalyzed conditions (Scheme C) . Cross-electrophile coupling reactions of aryl halides with various alkyl radicals to form C­(sp 2 )–C­(sp 3 ) bonds have the broad generality needed, but the use of aryl carboxylic acid esters under these conditions has been demonstrated to make ketone products, not alkylated arenes (Scheme A) .…”
mentioning
confidence: 99%
“…A potential solution is the coupling of a carboxylic acid ester with an amine-derived (via N -alkyl pyridinium salts) or alcohol-derived (via alkyl halide) alkyl radical source under nickel-catalyzed conditions (Scheme C) . Cross-electrophile coupling reactions of aryl halides with various alkyl radicals to form C­(sp 2 )–C­(sp 3 ) bonds have the broad generality needed, but the use of aryl carboxylic acid esters under these conditions has been demonstrated to make ketone products, not alkylated arenes (Scheme A) .…”
mentioning
confidence: 99%
“…Our laboratory recently reported the palladium-catalyzed unimolecular fragment coupling (UFC) of amides, in which an amide moiety is deleted from the substrate (Scheme 1b , top). 6e In this reaction, an amide group is eliminated in the form of an isocyanate. In our preliminary study, we also found that when amide substrates bearing an unprotected alcohol group are used, the eliminated isocyanate is trapped by the alcohol moiety (Scheme 1b , bottom).…”
mentioning
confidence: 99%
“…In our previous deisocyanative UFC, the trimerization of the eliminated isocyanate to form a stable cyclic trimer (i.e., isocyanurate) serves as one of the driving forces for this reaction. 6e In contrast, in this migratory UFC, the eliminated isocyanate is captured by a tethered nucleophile before it trimerizes. To obtain insights into the thermodynamics of these processes, the free energies of starting thiocarbamate 1a , UFC product 7 , isocyanate 8 , cyclic trimer 9 , and migratory UFC product 2a were estimated by DFT calculations (Figure 1 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations